Higher education for people with ogranichnnymi opportunities in South Korea - Kudaibergenova R. Е. (Journal of Oriental Studies, 2016)
Main purpose of the paper is to research reformation and modernization of special education in the republic of Korea and challenges of higher education development. the idea of this paper appeared from perception of importance of creation of conditions for accessible education for disabled children and adults and successful progressive development of this sphere in south Korea. the objective of the paper is to research south Korea experience and formulate and implement the modernization program of education for disabled people in Kazakhstan.